Loop Algorithms for Ductility Analysis of Column Reinforced Steel with Yield Strength Above 500 MPA - Ahmad Faza Azmi (JEECS (Journal of Electrical Engineering and Computer Sciences), 2021)
There are many benefits to the use of high-strength reinforcement (above 500 MPa) in reinforced concrete buildings. The advantages of using high-strength reinforcement are reduction steel volume and dimension, reduced construction time, reduction in reinforcement congestion, as well as savings in materials and worker cost. Meanwhile, the investigation of ductility of reinforced concrete element with high-strength reinforcement to resist earthquake effects under current design procedure is needed. In the current standard, ACI 318-71, The maximum specified yield strength was restricted to 60 Ksi (413 MPa) for reinforcement in special seismic system. There were also no ASTM standard specifications for reinforcement with yield strength above 500 MPa. In the design of seismic resisting structures, the analysis of curavture ductility and flexural overstrength factor is of important consideration in order to avoid brittle failure. This paper attempts to anaylze the ductility and re-evaluate the flexural overstrength factor of reinforced concrete column. The tensile tests of steel reinforcement with yield strength above 500 MPa generates stress-strain curve. An idealisations for the monotonic stress-strain curve proposed by mander was adopted in this study. Whereas in this numerical study of confined concrete columns, the behavior of concrete cored is modeled by the stress-strain relationship of confined concrete proposed by Kappos-Konstantinidis. This stress strain model was used for the momen, curvature, ductility, and flexural overstrength factor analysis.